2012
DOI: 10.1557/jmr.2012.294
|View full text |Cite
|
Sign up to set email alerts
|

Insight into reactions and interface between boron nitride nanotube and aluminum

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 58 publications
1
36
0
1
Order By: Relevance
“…8). Thus the present results support the conclusion of Lahiri et al [30] who found that the rate of new phase formation at the Al/BNNT interface is very slow. The observed reaction products suggest the formation of strong bonds between the Al matrix and reinforcing BNNPs.…”
Section: Microstructuresupporting
confidence: 93%
See 3 more Smart Citations
“…8). Thus the present results support the conclusion of Lahiri et al [30] who found that the rate of new phase formation at the Al/BNNT interface is very slow. The observed reaction products suggest the formation of strong bonds between the Al matrix and reinforcing BNNPs.…”
Section: Microstructuresupporting
confidence: 93%
“…In this regard it can be pointed out that the formation of both AlN and AlB 2 phases was only observed during exposure at a slightly higher temperature than the sintering temperature of 600 o C utilized by us, i.e. near the melting point of Al (650 o C) for 60 min, but the thickness of reaction-product layer was very small, about 1.5 nm [30].…”
Section: Microstructurementioning
confidence: 60%
See 2 more Smart Citations
“…[11][12][13][14][15][16][17][18] Spark plasma sintering (SPS) is one of the popular consolidation techniques, and is desirable since it involves lower sintering temperature and soaking times as compared to conventional sintering techniques. [11][12][13][14][15][16][17][18] Spark plasma sintering (SPS) is one of the popular consolidation techniques, and is desirable since it involves lower sintering temperature and soaking times as compared to conventional sintering techniques.…”
Section: Introductionmentioning
confidence: 99%